Enhancing English as a foreign language university students’ writing through explicit instruction of conjunctions as cohesive devices: An experimental study - Alawerdy, Arwa Saleh; Alalwi, Fahd Shehail (Frontiers in Psychology, 2022)
Cohesion has long been regarded as one of the main components of successful writing, a belief that seemed to be confirmed by Halliday and Hasan (1979). The basic assumption of this concept is that the interpretation of one element in a text is based on the interpretation of another in the same text. It has been noticed that Saudi EFL students seem to lack some basics in writing a cohesive paragraph. Certain conjunctions were overused, underused, or misused. The present empirical study, therefore, attempted to investigate the impact of explicit teaching of conjunctions as cohesive devices on the development of paragraph writing. The subjects of this study were 43 EFL students at a Saudi University studying in the first year. Data were collected from pre and post tests and analyzed qualitatively and quantitatively. Results showed significant differences between the experimental and control groups in the post test. Pedagogical implications are presented.